Occupational Health Requirements in Trinidad and Tobago: Integrating the Occupational Safety and Health Act and Employer Legal Mandates for Improved Worker Health - Joshua Jogie; Vandana Mannah, (International Journal of Preventive Medicine and Health (IJPMH), 2025)
This review examines the legal framework for occupational health in Trinidad and Tobago. It focuses on the Occupational Safety and Health Act and other employer requirements. The review discusses how these laws protect worker health and improve workplace safety. We analyzed official documents, government guidelines, and current research. The review highlights key provisions of the legal framework. It identifies areas where the law benefits workers and points out challenges in enforcement. Some gaps in implementation can affect worker safety and overall health outcomes. The review also discusses the impact of these legal requirements on the healthcare system. It considers how legal mandates contribute to reduced workplace injuries and better health practices. We suggest measures for improving compliance and monitoring. Our findings indicate that clear legal standards help create safer work environments. The review is relevant for health professionals, employers, and policymakers. It offers insights into how legal measures can enhance public health. Future research is needed to assess the long-term benefits of these occupational health laws in Trinidad and Tobago.